PRACTICING DISCUSSION IN THE FORM OF PYRAMID TO IMPROVE STUDENTS’ SPEAKING PERFORMANCE AND CLASSROOM INTERACTION - Buhari, Buhari (JOLLT Journal of Languages and Language Teaching, 2019)
Speaking is an ability to use the language in oral form to express what is on language learners? thinking. Learners have speaking skills if they have skills to practice grammar, comprehension, vocabulary, pronunciation, and fluency in the oral form. To attain the speaking skills, English teachers are encouraged to meet an appropriate learning strategy to be applied in the speaking classes. This study is a collaborative classroom action research. It is aimed at describing how the use of pyramid discussion to enhance students? speaking performance and classroom interaction. Its steps consisted of Planning, Acting, Observing, and Reflecting. This research was conducted at the 8th-grade students of SMPN 1 Praya Timur, Central Lombok. There were three instruments employed to obtain the data namely test, observation sheet, and questionnaire. After having the cycle 1, the findings showed that there were 16 students who got score more than 70. The calculation of the mean score was 77.30. Meanwhile, the tabulation of the percentage was 88.90. The data of the observation sheet indicated that the students were enthusiastic in classroom interaction and they feel interested in learning English. The research findings showed that the mean score was 83.22. It could be concluded that the use of pyramid discussion was able to improve students? speaking performance and classroom interaction at the 8th-grade students of SMPN 1 Praya Timur, Central Lombok.